The Influence of Fintech Payment, Financial Literacy, and Social Environment on Financial Management in College Students - Nurul Tsalatsa Azizah; Mukhzarudfa; Muhammad Gowon (Greenation International Journal of Economics and Accounting, 2025)
This study aims to determine the influence of Fintech Payment, Financial Literacy and Social Environment on Financial Management in Students. The questionnaire was distributed to accounting students of the 2021-2024 batch of the University of Jambi with a total of 256 valid and processable questionnaires. Data processing is carried out using SPSS Version 27. The results of the study indicate that first, Fintech Payment does not have a partial effect on Financial Management. Second, Financial Literacy has a significant partial effect on Financial Management. Third, the Social Environment has a significant partial effect on Financial Management. Fourth, Fintech Payment, Financial Literacy and Social Environment have a simultaneous effect on Financial Management